DISCOURSE ON THE DISCOVERY AND RENEWAL OF THE PRINCIPLE OF LEGALITY IN CRIMINAL LAW - Mufty, Abdul Malik; Nur, Nurul Chaerani (fakultas hukum universitas PGRI Semarang, 2024)
The principle of legality was created to limit the arbitrary actions of kings/rulers against their people. Power has the ability to punish individuals, even though it is not regulated in advance. However, the form of power is the most important factor in determining whether an action can be punished. The function of protecting victims or people is not fulfilled by the principle of legality. Law No. 1 of 2023 regulates the Criminal Code which is a significant reform. Law No. 1 of 2023 is marked by the recognition and implementation of implicit laws that apply in society, while also recognizing the existence of legal certainty and positive law.Â The purpose of this study is to analyze the discovery and application of the principle of legality in Law No. 1 of 1946 and examine the renewal of the principle of legality in Law No. 1 of 2023. This study uses normative research methods to support secondary data. The findings of this study show that the concept of the principle of legality was introduced in 1748 as a means to prevent arbitrary actions by kings or tyrants against their people. The court can process and try customary crimes or acts that are contrary to applicable legal values but there is no equivalent or comparison in Law No. 1 of 2023 as a result of the expansion of the principle of legality.